IMPACT OF JOB CRAFTING ON EMPLOYEE PRODUCTIVITY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Anriyani; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the differentiated impact of job crafting dimensions—task, relational, and cognitive—on employee productivity and organizational citizenship behavior (OCB). Analyzing data from a diverse workforce, the research employed regression analysis to test its hypotheses. The findings reveal a distinct predictive pattern: task crafting emerged as the strongest, most significant predictor of enhanced employee productivity, as employees who optimized their core tasks demonstrated greater efficiency and output. Conversely, relational crafting was the most powerful driver of OCB, fostering altruism, teamwork, and cooperative behaviors. Cognitive crafting showed a moderate influence. These results validate and refine the Job Demands-Resources model, demonstrating that employees proactively build specific resources to achieve targeted outcomes. The study provides a clear blueprint for organizations, suggesting that interventions to boost productivity should empower task restructuring, while fostering relational crafting is key to building a cooperative organizational climate.